The work of Jaroslav Pelikan on Insects of the order Thysanoptera. - Fedor, Peter J.; Mound, Laurence A. (Contributions to Entomology = Beiträge zur Entomologie, 2007)
The paper is a small tribute to Doc. Ing. Dr. Jaroslav Pelikán, DrSc, who has been a reputable scientist in the fields of entomology, theriology and ecology. He described about 80 new species of thrips as well as seven new genera of Thysanoptera. His national contributions included several checklists, together with his more complex contribution within the Fauna of Czechoslovakia. On the 22nd of April 2006 Jaroslav Pelikán celebrated his 80th birthday.